An Exploratory Study on Job Satisfaction and Work Performance of Health Care Nurses: Exploring the Impact of Work Environment on Job Satisfaction and Performance of Health Care Nurses (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This paper examined the nature of the work environment of communityhealth nurses, and determined the level of job satisfaction among these nurses.It further explored the relationship between work environment and jobsatisfaction of these nurses, and perceived factors in the work environmentthat would increase their job satisfaction. Job satisfaction, quality of workenvironment and morale of health practitioners is beginning to receiveattention worldwide. The efficiency of an organization depends largely on themorale of the employees. Job satisfaction of the health workers is said to behighly important in building up employee motivation and efficiency as higherjob satisfaction determine better employee performance and higher level ofpatients’ satisfaction. It has been observed that when health professionals aresatisfied with their job as a result of presence of key elements in theworkplace that strengthen and support the workforce, rates of absenteeism andturnover intent usually decrease, staff morale and productivity increase andwork performance as a whole improves.